“Parto podálico con feto único y su relación con el apgar del recién nacido, en el hospital apoyo Iquitos “cesar Garayar Gracía” Períoro Octubre 1995 – Setiembre 1996 - Torres Trigozo, Kelly (1997)
The present study is cohort, was carried out in the city of Iquitos in the Hospital support Cesar Garayar Garcia through surveys and interviews aimed at patients. The universe was composed of n = 150 pregnant women Primiparous and multiparous; of which n1 = 75 constituted the study group and q = 75 control group. The corresponding statistical analysis showed as a result: the lack of birth Control Pre and gestational age; ·eran the two main factors that conditioned the gastropathy childbirth. This presentation dystocia prevention is hampered by factors such as: low accessibility to hospitals, the factor of Socio-economic, the degree of instruction and the marital status, situation that allows to say that these factors are the gue interfere to end pregnancy with a normal delivery.